Influence of iron ore concentrate on the characteristics of sintering and reduction of sinter - Guo H.; Shen F.-M.; Jiang X.; Xiang D.-W.; Zheng H.-Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
As Australia is the main iron ore importing country for China, the abundant mineral resources of Australia are the primary raw materials for the sintering process. To better understand the properties of different iron ores from Australia and then guide the sintering process, this study selected four types of Australian ore and one type of domestic ore, and their properties were investigated under different conditions. The experiment of single iron ore sintering was studied to examine the influence of different iron ores on the metallurgical properties of sinter. From this study, the following results were obtained: GG showed poor fluidity and higher assimilability temperature, but the bonding phase strength was the highest; YD showed better fluidity and lower assimilability temperature, whereas SJY (domestic ore) showed better fluidity and higher bonding phase strength, and lower assimilability temperature. The influence mechanism of iron ore on the fluidity was further analyzed by using SEM and ion theory of slag. With the increase SiO2 content of iron ore, the fluidity index increased, the main reason was that the amount of liquid phase increased and the melting point decreased during the sintering. However, an excessive amount of SiO2 caused the decrease of fluidity index of iron ore; the main reason was that the fluidity of the liquid phase itself decreased and secondary hematite appeared. In the case of the higher SiO2 content of iron ore, the main bonding phase was calcium silicate. With the decrease of SiO2 content, the calcium silicate transformed into calcium ferrite. The main reason for this was that the Gibbs free energy of calcium ferrite and dicalcium ferrite (2CaO·SiO2) was higher than that of calcium silicate in the temperature ranges of 400-1600 K. The reduction degree of YD was the highest in all the cases and that of GG was the lowest. Activation energies of 5.39, 3.14, 3.51, 4.47 and 2.92 kJ/mol were obtained for the reduction of GG, PB, BH, SJY, and YD, respectively. In all the cases, the reaction corresponded to the model function of F1(α), and the integral form was -ln(1-α)=kt. Through this investigation, it could be concluded that the most appropriate ore category for sinter pot was YD.